2000
DOI: 10.1097/00004694-200003000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We prospectively followed 27 consecutive children with tibial circular external fixators applied between July 1, 1995, and June 30, 1997. A simple pin care system with no physical pin cleansing except that provided by daily showers was used. Children with inflamed or infected pin sites were placed on an oral antibiotic (cephalexin) for 10 days. Pin sites were graded according to the system of Dahl et al. on a 0 to 5 scale. A total of 4,473 observations was made. Patients developed 178 pin tract infections (4.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…however a number of studies reported significant complications such as infection, delayed union, refracture, limb overgrowth, malunion, need for remanipulation, and joint stiffness 24–29. Complications related to pin site problems have been well described in tibial external fixation 3334. Henley et al .…”
Section: Discussionmentioning
confidence: 99%
“…however a number of studies reported significant complications such as infection, delayed union, refracture, limb overgrowth, malunion, need for remanipulation, and joint stiffness 24–29. Complications related to pin site problems have been well described in tibial external fixation 3334. Henley et al .…”
Section: Discussionmentioning
confidence: 99%
“…One such meeting was the Royal College of Nursing meeting held in the United Kingdom in 2010, which published their guidelines in 2011 [32]. In lieu of this, there are still a myriad of protocols available, ranging from a nihilistic approach with no active pin site care [29], to twice daily cleaning and dressings plus oral antibiotics for the entire duration of the external fixator [3]. …”
Section: Pin Site Carementioning
confidence: 99%
“…The appropriate time to commence pin track care vary greatly in the literature with published times ranging from 24 h to 10 days [2, 3, 5, 10, 2729, 31]. The frequency of pin track cleaning also differ, with authors suggesting once daily [6, 27], twice daily [3, 4], weekly [27, 33] or ‘when required’ [28].…”
Section: Pin Site Carementioning
confidence: 99%
“…Regarding pin tract infection, we reported 12 grade 1 (pain, erythema, or tenderness around the pin site), 8 grade 2 (characteristics of grade 1 infections plus serous drainage) and 5 grade 3 (characteristics of grade 1 infections plus purulent drainage) according to Gordon’s grading system [13]. Pin-site infections were treated by oral antibiotics (amoxicillin) [14, 15] except for one, which required intravenous antibiotics and one half-pin removal without compromising the frame’s stability.…”
Section: Resultsmentioning
confidence: 99%